Get ready for 2nd grade. (New York : Scholastic, 2004)
Contains stickers, activities, and worksheets designed to help children improve their math, phonics, grammar, writing, and reading skills before entering second grade.
Includes stickers and game board.
Professional.
Professional
Keywords: Creative activities and seat work; Education, Elementary; Second grade (Education); Teaching -- Aids and devices; Creative activities; Elementary education; Second grade (Education); Teaching -- Aids and devices